Using Group Velocity for Correct Determination of Phase Coefficient Without Initial Phase Assumption - Lomakin, Konstantin; Helmreich, Klaus; Gold, Gerald (2020 IEEE 24th Workshop on Signal and Power Integrity (SPI), 2020)
In this paper, an approach is proposed that allows to measure the absolute quantity of guided wavelength and phase coefficient of arbitrary transmission line types. By using the group velocity as a derivative quantity of the phase coefficient, ambiguities within the logarithm of complex values can be resolved. The typically unknown initial phase coefficient offset of band limited measurements can be acquired by the proposed approach without the need for assumptions concerning the transmission line type and acquisition of its explicit cross section geometr